2005
DOI: 10.1136/jcp.2004.024380
|View full text |Cite
|
Sign up to set email alerts
|

A population based seroepidemiological survey ofChlamydia pneumoniaeinfections in schoolchildren

Abstract: Aim: A serosurvey was carried out in schoolchildren from a northeastern area of Italy to define the burden of Chlamydia pneumoniae infection. Methods: A sample of 649 schoolchildren underwent a simplified version of the International Study of Asthma and Allergies in Childhood questionnaire and IgG and IgA antibodies were investigated using an enzyme immunoassay, followed by a microimmunofluorescence assay in reactive sera. Results: Of the children examined, 29% and 19.7% had IgG and IgA antibodies, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
6
0
2
Order By: Relevance
“…For C. jejuni, an annual incidence of 0.5-1.1% has been published, which is about one half that found in our group of GBS children [21,28]. The infection rate with C. pneumoniae in children has been found to be 2.2-9.2/100 person-years, depending on the age group [1,7]. IQR, Interquartile range; Maxdis, disability score at maximum of disease (0: normal; 1: able to run; 2: able to walk 5 m unaided; 3: able to walk with aids; 4: not able to walk; bed-or chair-bound; 5: bed-bound, cannot raise legs; 6: intubated, on artificial ventilation); plateau, days of plateau phase; improvement, days to improve from first symptoms; walk, days to walk unaided from first symptoms; free, days to be free of symptoms from first symptoms The seroconversion rate for CMV similarly varies between 6 and 12/100 person-years [44].…”
Section: Discussionmentioning
confidence: 87%
“…For C. jejuni, an annual incidence of 0.5-1.1% has been published, which is about one half that found in our group of GBS children [21,28]. The infection rate with C. pneumoniae in children has been found to be 2.2-9.2/100 person-years, depending on the age group [1,7]. IQR, Interquartile range; Maxdis, disability score at maximum of disease (0: normal; 1: able to run; 2: able to walk 5 m unaided; 3: able to walk with aids; 4: not able to walk; bed-or chair-bound; 5: bed-bound, cannot raise legs; 6: intubated, on artificial ventilation); plateau, days of plateau phase; improvement, days to improve from first symptoms; walk, days to walk unaided from first symptoms; free, days to be free of symptoms from first symptoms The seroconversion rate for CMV similarly varies between 6 and 12/100 person-years [44].…”
Section: Discussionmentioning
confidence: 87%
“…Ten pediatric asthma studies from 7 countries met inclusion criteria (Table 1) [12][13][14][15][16][17][18][19][20][21]. Nine studies reported peripheral blood biomarkers (serology in 8, culture in 1) and 1 reported on nasal and/or induced sputum specimens.…”
Section: Updated Systematic Reviewmentioning
confidence: 99%
“…Las infecciones por C. pneumoniae comienzan a ocurrir a partir de los últimos años de la niñez, su mayor incidencia tiene lugar en varones jóvenes, pero puede presentarse en adultos de cualquier edad (29). C. pneumoniae es un germen ubicuo, ya que más del 40 % de la población adulta posee anticuerpos contra el mismo.…”
Section: Epidemiologíaunclassified